Subjective Well-Being Of Russian Female Personnel As An Indicator Of Socio-Psychological Age - Leonova, Irina S.; Zakharova, Liudmila N.; Bretones, Francisco D. (Opción, 2019)
The present work is theoretical and empirical research on the socio-psychological age of female personnel at enterprises with different organizational cultures. The main indicators of socio-psychological age include the level of commitment to organizational values, readiness for organizational changes, involvement in labor activity, and fatigue. The respondents are female employees of two large industrial enterprises. The female personnel working in a market-hierarchical type of organizational culture with an expressed innovative component reflect characteristics of a younger socio-psychological age while those working at an enterprise with a hierarchical-clan type of organiza- tional culture display characteristics of a more senior socio-psychological age.